High speciation in the cryptic Pristimantis celator clade (Anura: Strabomantidae) of the Mira river basin, Ecuador-Colombia - Mario H. Yánez-Muñoz; Juan P. Reyes-Puig; Carolina Reyes-Puig; Gabriela Lagla-Chimba; Christian Paucar-Veintimilla; Miguel A. Urgiles-Merchán; Julio C. Carrión-Olmedo (PeerJ)
Over the past decade, research in the montane forests of the Mira River basin, spanning Ecuador and Colombia, has identified it as crucial for the adaptive radiation of flora and fauna, shaped by its complex geological and climatic history. This study focuses on the phylogenetic and systematic revision of a frog clade initially labeled as Pristimantis verecundus, revealing significant cryptic diversity. Through detailed analyses of type material and expanded molecular sampling, we found that the original description actually included specimens representing two additional species, which are described herein. In this work, we discovered and formally described four new species within montane forests at elevations from 1,600 to 2,300 meters. Genetic distances of 3.34% to 14% and clear morphological differences underscore the clade’s hidden diversity. We propose renaming the group Pristimantis celator clade within Pristimantis myersi species group and subgenus Trachyphrynus, aligning with phylogenetic evidence and resolving taxonomic ambiguities using the oldest available name, Pristimantis celator (Lynch, 1976). This reclassification includes 14 species, seven formally described, and seven as candidates, distributed across northwestern Ecuador and southwestern Colombia, particularly in Mira and Esmeraldas River basins. The study highlights the Andean orogeny’s role in species diversification within Pristimantis celator clade, with geographic barriers like Cerro Golondrinas influencing genetic isolation. Genetic divergences exceeding 3.34% indicate evolutionary isolation across these landscapes. Our findings provide insights into montane ecosystem speciation, emphasizing vicariance, niche adaptation, and altitudinal gradients in shaping biodiversity. A polytomy among three well-supported clades within Pristimantis myersi species group is noted due to incomplete genetic data, yet distinctiveness and evolutionary relationships are affirmed. Cryptic diversity within Pristimantis celator clade links to unique orogenic and climatic conditions, highlighting conservation needs. Lastly, we provide a redescription of Pristimantis verecundus and species identification key to aid future research and conservation in this biogeographically influential region.